Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5152/ejp.2014.43534
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in Smoking Habits of Active Smoker Health Care Professionals after the ‘Law on Prevention of Harmful Effects of Tobacco and Tobacco Products’

Abstract: Objective: To evaluate the approaches of active-smoker health care workers to the law on "Prevention and Control of Hazards of Tobacco Products", to determine behavioral changes in smoking and the factors associated with these changes after the law was enacted. Methods:The population of the study consisted of 1096 health care workers who were active smokers and worked at state hospitals and the 112 emergency service in Çorum. Questionnaire forms were delivered by hand to the participants. The survey was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results of the same study showed that those who had tried to quit smoking previously had a statistically significant positive response to the ban [17].…”
Section: Discussionmentioning
confidence: 90%
“…The results of the same study showed that those who had tried to quit smoking previously had a statistically significant positive response to the ban [17].…”
Section: Discussionmentioning
confidence: 90%
“…Although smoking is a fairly regular activity and a top-up of nicotine dosage is sought throughout the day, smoking behavior changes dramatically in some specific situations mentioned earlier. These changes in smoking patterns include the ability to postpone or modify smoking behavior without experiencing severe symptoms of abstinence and cravings (Türkkani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%